2021
DOI: 10.1515/jpem-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

The presentation of congenital adrenal hyperplasia in an unscreened population

Abstract: Background The aim of this study was to describe the incidence and spectrum of early clinical presentations of congenital adrenal hyperplasia (CAH) in an unscreened population. Methods A national retrospective observational study was undertaken to identify all children diagnosed with CAH in the Republic of Ireland, between January 2005 and December 2019. Reporting clinicians completed anonymized clinical questionnaires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Prior to inclusion of SCID on the panel earlier this year, a study showing its high prevalence in Ireland and the need for NBS was reported in 2021 [ 849 ]. Studies supporting the addition of other conditions have also been recently published including one on CAH and another on metachromatic leukodystrophy [ 850 , 851 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior to inclusion of SCID on the panel earlier this year, a study showing its high prevalence in Ireland and the need for NBS was reported in 2021 [ 849 ]. Studies supporting the addition of other conditions have also been recently published including one on CAH and another on metachromatic leukodystrophy [ 850 , 851 ].…”
Section: Resultsmentioning
confidence: 99%
“…The value of NBS for CAH has been debated, and despite international endocrine societies recommending its use [2, 48], it is not currently universally adopted [3, 4, 6, 7, 28]. Screening for CAH significantly reduces the time to diagnosis [9, 10, 49] and thus has the potential to reduce mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Where screening programmes account for age at collection times with adjustment of 17OHP cutoffs, the number of early false positives will be reduced [31,32]. Screening later is attractive, as it reduces many of these confounding factors; however, allowing for the turnaround time, there is a risk that infants may present symptomatically if there is a delay in screening result, thereby reducing the potential benefits of NBS [28]. Screening programmes must also take into consideration other conditions within their NBS panel, ease of arranging NBS (e.g., where many infants are discharged early), local infrastructure (for transit of samples), and availability of laboratory resources, in order to appropriately balance the risks of false-positive results and the urgency to detect affected infants in their area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, enhanced ROS may contribute to the induction of autophagy in the retina. Another mechanism of mitochondrial dysfunction leading to DR is the formation of free radicals[ 14 - 17 ]. These reactive compounds may contribute to a switch in the metabolism, e.g.…”
Section: Introductionmentioning
confidence: 99%